2020
DOI: 10.1111/all.14634
|View full text |Cite
|
Sign up to set email alerts
|

Systemic allergic reactions induced by labile plant‐food allergens: Seeking potential cofactors. A multicenter study

Abstract: Background Heat‐and‐pepsin‐sensitive plant food allergens (PR‐10 and profilin) sometimes cause systemic reaction. Objective To detect the risk factors for systemic reactions induced by labile food allergens. Methods A retrospective multicenter study was performed on patients with a documented history of systemic allergic reaction to labile plant food allergens and on age‐matched controls with a history of oral allergy syndrome (OAS) induced by the same foods. Offending foods, their amount, and state (solid or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…Although we found more severe and critical COVID-19 cases in patients with asthma than that reported from China, no significant difference was shown compared to that in patients without asthma. Therefore, our results support the emerging idea that patients with underlying comorbidity of asthma are not at higher risk of severe COVID-19 infection [ 9 , 28 ]. However, it is still unclear whether SARS-CoV-2 would increase asthma exacerbation although viral infection is recognized as one of the risk factors for asthma exacerbation, therefore, further investigations on this aspect are needed.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Although we found more severe and critical COVID-19 cases in patients with asthma than that reported from China, no significant difference was shown compared to that in patients without asthma. Therefore, our results support the emerging idea that patients with underlying comorbidity of asthma are not at higher risk of severe COVID-19 infection [ 9 , 28 ]. However, it is still unclear whether SARS-CoV-2 would increase asthma exacerbation although viral infection is recognized as one of the risk factors for asthma exacerbation, therefore, further investigations on this aspect are needed.…”
Section: Discussionsupporting
confidence: 86%
“…The possibility of a type-2 deviated immune response during viral infections has been speculated [ 8 ]. Th2-skewed immunity down-regulates type I and III interferon productions, which are the key contributors of late-phase hyperinflammation in severe respiratory viral diseases [ 9 ], and the deficiency in interferons is also linked to the impaired innate antiviral immune responses in asthma [ 10 ]. Existing data on asthma as a risk factor for COVID-19 is contradictory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a clear lack of evidence in the case of COVID-19 despite the claim that asthma is one of the comorbidity in some cohorts [ 92 ]. The rate of asthmatics infected seems low compare to the normal population rate in some other country and their odds ratio toward severity was not increased [ 149 , 150 ]. This would go in line with a study comparing COPD and asthma, showing that asthmatic patients in contrast showed a lower risk of severe outcome compared to COPD [ 151 ].…”
Section: Etiology Of Sars-cov-2mentioning
confidence: 99%
“…According to their results, PR -10 proteins and profilininduced systemic reactions are facilitated by PPI, ingestion of large amounts of unprocessed foods, and fasting. Soybean beverages represent a risk for PR -10 hypersensitive patients and should be avoided (Asero et al, 2020).…”
Section: Discussionmentioning
confidence: 99%